Homoenxerto aórtico criopreservado no tratamento cirúrgico das lesões da valva aórtica: resultados imediatos - Gerola, Luís Roberto [UNIFESP] (2004)
OBJECTIVE: To assess immediate clinical and echocardiographic results of the use of cryopreserved aortic homografts for aortic valve replacement. METHODS: Eighteen patients with aortic valve disease underwent aortic valve replacement, receiving a cryopreserved aortic homograft, 15 were male, 10 had aortic regurgitation, and 8 had aortic stenosis. Age ranged from 18 to 65 years (mean, 44.5 ± 18.14 years). Four patients had infective endocarditis, 12 patients were in functional class II, and 6 patients were in functional class III (NYHA). Left ventricular function was normal in 15 patients. RESULTS: Hospital mortality was 5.5% (1 patient) due to respiratory distress; the other patients were discharged from the hospital between the fifth and eighth postoperative days in functional class I. Maximal aortic transvalvular gradient, on echocardiography, ranged from 0 to 30 mmHg, with a mean of 10.9 ± 9.2 mmHg. Five patients did not have any degree of regurgitation through the aortic homograft, 11 patients (61.1%) had minimal regurgitation, and 2 had mild regurgitation. Duration of extracorporeal circulation ranged from 130 to 220 minutes (mean, 183.9 ± 36.7 minutes). Duration of aortic clamping ranged from 102 to 168 minutes (mean, 139.14 ± 25.10 minutes). Bleeding in the postoperative period ranged from 210 to 1220 mL, with a mean of 511.4 ± 335.1 mL. Reoperations were not necessary. Duration of orotracheal intubation ranged from 2 hours 50 minutes to 17 hours with a mean of 9.14 ± 3.6 hours. CONCLUSION: Cryopreserved aortic homografts may be routinely used with low hospital morbidity and mortality.